2008
DOI: 10.1093/brain/awn198
|View full text |Cite
|
Sign up to set email alerts
|

Persistent inflammation alters the function of the endogenous brain stem cell compartment

Abstract: Endogenous neural stem/precursor cells (NPCs) are considered a functional reservoir for promoting tissue homeostasis and repair after injury, therefore regenerative strategies that mobilize these cells have recently been proposed. Despite evidence of increased neurogenesis upon acute inflammatory insults (e.g. ischaemic stroke), the plasticity of the endogenous brain stem cell compartment in chronic CNS inflammatory disorders remains poorly characterized. Here we show that persistent brain inflammation, induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
221
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(234 citation statements)
references
References 39 publications
12
221
0
1
Order By: Relevance
“…However, similar to human AD patients immunized with Ab (Elan's trial), the immunized mice develop meningoencephalitis presumably due to T cell activation at the perivascular/subarachnoid space prior to crossing the glia limitans. Similar effects of T cell activation at the brain vasculature were also described in MS (14) and are likely to impair the brain-endogenous capacity for cell renewal and repair (48,49). In contrast, because activated T cells in the current study were injected directly into the lateral ventricle, no further activation was required prior to crossing the epithelial layer or the vasculature's glia limitans into the brain parenchyma, and, as such, the injected cells induced neither significant vascular pathology nor cellular apoptosis, but instead, similar to previous studies demonstrating the positive effects of T cells and IFN-g on neurogenesis (24, 27, 50, 51), slightly enhanced hippocampal neurogenesis in an age-dependent manner.…”
Section: Discussionmentioning
confidence: 64%
“…However, similar to human AD patients immunized with Ab (Elan's trial), the immunized mice develop meningoencephalitis presumably due to T cell activation at the perivascular/subarachnoid space prior to crossing the glia limitans. Similar effects of T cell activation at the brain vasculature were also described in MS (14) and are likely to impair the brain-endogenous capacity for cell renewal and repair (48,49). In contrast, because activated T cells in the current study were injected directly into the lateral ventricle, no further activation was required prior to crossing the epithelial layer or the vasculature's glia limitans into the brain parenchyma, and, as such, the injected cells induced neither significant vascular pathology nor cellular apoptosis, but instead, similar to previous studies demonstrating the positive effects of T cells and IFN-g on neurogenesis (24, 27, 50, 51), slightly enhanced hippocampal neurogenesis in an age-dependent manner.…”
Section: Discussionmentioning
confidence: 64%
“…Mouse neural precursor cells (NPCs), donated by Dr. Stefano Pluchino (University of Cambridge, U.K.), were prepared and cultured as described 14.…”
Section: Methodsmentioning
confidence: 99%
“…Periodontopathic bacteria possess a number of potential virulence factors and induce host inflammatory mediators, eventually leading to connective tissue degradation and alveolar bone resorption. 5 Studies have shown that the presence of chronic inflammation might compromise the migration, proliferation and availability of stem cells in multiple sclerosis 6 and atherosclerosis. 7 Regarding periodontal disease, an in vitro study showed that exposure to the etiological factors induced apoptosis in periodontal ligament cells.…”
Section: Introductionmentioning
confidence: 99%